1996
DOI: 10.1017/s0031182000065148
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the presence of an infectious proportion amongst populations of Steinernema feltiae (Site 76 strain) infective stages

Abstract: SUMMARYExperimental studies were conducted on the proportion of Steinernema feltiae Filipjev (Site 76 strain) infective stages that infected Galleria mellonella L larvae, in sand tube assays. A full statistical analysis of the sand assay tubes was also undertaken. The analysis showed that the sand tubes were not a significant source of variation. Consequently the observed behaviour of the infective stages was considered to be due to a biological effect. The study shows that the proportion of infective stages t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 4 publications
5
39
0
Order By: Relevance
“…This calls into doubt the existence of phased infectivity sensu Bohan and Hominick in these species (or at least the strains tested). However, the temporal changes in infectivity reported by Bohan and Hominick (1996) may represent more subtle changes in infectivity-i.e., phased infectivity sensu GriYn (1996). GriYn (1996) reported an increase in the infectivity of H. megidis IJs stored at 20°C, reaching a peak after 3 weeks.…”
Section: Phased Infectivitymentioning
confidence: 99%
“…This calls into doubt the existence of phased infectivity sensu Bohan and Hominick in these species (or at least the strains tested). However, the temporal changes in infectivity reported by Bohan and Hominick (1996) may represent more subtle changes in infectivity-i.e., phased infectivity sensu GriYn (1996). GriYn (1996) reported an increase in the infectivity of H. megidis IJs stored at 20°C, reaching a peak after 3 weeks.…”
Section: Phased Infectivitymentioning
confidence: 99%
“…However, for the entomopathogenic nematodes, both heterorhabditids and steinernematids, changes in infectivity occur prior to the eventual decline associated with starvation (Fan & Hominick, 1991 ;Curran, 1993 ;Ishibashi, Wang & Kondo, 1994 ;Griffin, 1996 ;Bohan & Hominick, 1997). Two hypotheses have been proposed to explain this so-called ' phased infectivity '.…”
Section: Introductionmentioning
confidence: 99%
“…Campbell et al (1999) found evidence of a temporarily non-infectious proportion in Heterorhabditis bacteriophora, but not in 3 Steinernema species. An alternative hypothesis of phased infectivity proposed by Griffin (1995Griffin ( , 1996 assumes that the infectious individuals are not all physiologically and behaviourally identical, but that they vary in their infectivity (probability of penetrating a host per unit time). Fluctuations in the infectivity of a population may reflect underlying changes in the infectivity of individuals -either their ability or motivation to infect an insect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection by baiting gives an indication of the "killing power" of the soil, which is what matters in biocontrol; it can be argued that this is what matters in an ecological context also, as IJs that are not infective cannot reproduce. However, baiting may underestimate the persistence of ecologically relevant IJs if part of the population is temporarily non-infective (Bohan & Hominick, 1996, 1997Griffin, 1996).…”
Section: Fate Of the Inoculum: Death Or Dispersalmentioning
confidence: 99%